2006
DOI: 10.1007/s00426-006-0088-9
|View full text |Cite
|
Sign up to set email alerts
|

Fixed versus dynamic orientations in environmental learning from ground-level and aerial perspectives

Abstract: Ground-level and aerial perspectives in virtual space provide simplified conditions for investigating differences between exploratory navigation and map reading in large-scale environmental learning. General similarities and differences in ground-level and aerial encoding have been identified, but little is known about the specific characteristics that differentiate them. One such characteristic is the need to process orientation; ground-level encoding (and navigation) typically requires dynamic orientations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 57 publications
(80 reference statements)
6
48
1
Order By: Relevance
“…Within subjects effects and contrasts were Geisser-Greenhouse corrected for non-sphericity. We observed a significant main effect of orientation, Downloaded by [Uppsala universitetsbibliotek] at 04:48 11 October 2014 Previous studies using JRDs have not found consistent effects of sex (e.g., Shelton & McNamara, 1997, 2001a, 2001b, 2004a, 2004bShelton & Pippitt, 2007;Yamamoto & Shelton, 2005, 2009a, 2009b, and the direction of these effects, when observed on any given experiment, tends to be females more accurate than males as often as the reverse. There was no significant main effect of condition, F .2; 42/ D 1:537, p D 0:227.…”
Section: Resultscontrasting
confidence: 48%
See 1 more Smart Citation
“…Within subjects effects and contrasts were Geisser-Greenhouse corrected for non-sphericity. We observed a significant main effect of orientation, Downloaded by [Uppsala universitetsbibliotek] at 04:48 11 October 2014 Previous studies using JRDs have not found consistent effects of sex (e.g., Shelton & McNamara, 1997, 2001a, 2001b, 2004a, 2004bShelton & Pippitt, 2007;Yamamoto & Shelton, 2005, 2009a, 2009b, and the direction of these effects, when observed on any given experiment, tends to be females more accurate than males as often as the reverse. There was no significant main effect of condition, F .2; 42/ D 1:537, p D 0:227.…”
Section: Resultscontrasting
confidence: 48%
“…These results were consistent with subjective observations recorded during the model reconstruction task. The striking result was the lack of strong correspondence between the preferred orientation in JRDs and orientation of model reconstruction for the shared orientation condition, suggesting that these two tasks may tap into different aspects of the mental representation(s) formed during encoding as suggested by other types of cross-task comparisons (e.g., Shelton & McNamara, 2004a, 2004bShelton & Pippitt, 2007;Valiquette & McNamara, 2007).…”
Section: Resultsmentioning
confidence: 92%
“…In this study we examined older, cognitively normal APOE*4+ and APOE*4− subjects while they engaged in a perspective dependent spatial memory task which has been shown to activate the MTLs in young subjects (55,57). Separate encoding and recognition periods were evaluated to determine the extent that MTL activation is influenced by the APOE*4 allele and to explore if memory processing (encoding) and retrieval (recognition) are similarly affected.…”
Section: Introductionmentioning
confidence: 99%
“…An advantage of learning from a map is that it provides an overview of the environment that aids relational encoding; however, an advantage of learning through navigation is that there is no need to switch from an allocentric to an egocentric frame of reference. Maps typically also provide a stable orientation to the environment, unlike navigating from an egocentric view, which is very dynamic (Shelton & Pippitt, 2007). One general conclusion from this research is that people benefit from maintaining the same orientation and task goals (route or survey goal) during retrieval that were present during encoding (Taylor, Naylor, & Chechile, 1999).…”
Section: Category Adjustment Modelmentioning
confidence: 82%